The relationship between cognitive and social leisure activities across the lifespan and neural markers for brain health: A systematic literature review. (31st December 2021) - Duffner, Lukas; de Jong, Nathan; Backes, Walter H; Jansen, Jacobus FA; de Vugt, Marjolein; Deckers, Kay; Koehler, Sebastian
Abstract: Background: Cognitive and social leisure activities (CA/SA) as well as social network size (SNS) have been associated with performance on cognitive tasks and lower dementia risk. However, the neural mechanisms behind these associations remain unclear. Therefore, this systematic literature review aims at summarizing the available evidence on these associations across the adult lifespan. Method: MEDLINE, PsychINFO, CINAHL and the Cochrane Library of Controlled Trials were searched for potential publications until January 2021. Eligible studies included those with cognitively normal individuals older than 18 years, and assessed the direct association between CA/SA or SNS and brain structure. CA/SA were defined as those cognitively and/or socially stimulating activities being performed for the sake of pleasure. Eligible outcome measures included magnetic resonance imaging (MRI) of macro (grey/white matter volumes) and micro (diffusion tensor imaging) structure, or computerized tomography (CT). Both observational and (quasi)experimental designs were included. Study‐quality was assessed using the NIH tool for study quality appraisal and the Newcastle‐Ottawa Scale. This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. A full protocol is available in PROSPERO (CRD42020193278). Result: 6115 unique abstracts were identified and screened by two independent raters. Sixty‐six full‐text articles were retained for further appraisal, of which thirty‐five (0.6%) were included for qualitative analysis. Of those, 20 cross‐sectional, 4 cohort and 3 experimental studies investigated the association between CA/SA and brain structure. Eight cross‐sectional studies investigated the relationship between social network size and brain structure. All studies included in this review used structural MRI (3 used DTI) as outcome measure. In the majority of studies, CA/SA and SNS showed associations with structural brain MRI markers. Detailed results of this ongoing review and possible meta‐analysis will be presented. Conclusion: CA and SA are associated with structural MRI markers.